Don Quijote: The Econopoetics of Cervantes’s Epic Comedy - Brewer, Brian (Revista Canadiense de Estudios Hispánicos, 2023)
Critics have shown increasing interest in the economic discourse in Don Quijote, but most studies on the topic have focused on Cervantes’s possible political ideology or the ways in which his fiction might reflect long-term socioeconomic changes, such as the transition from late feudalism to early capitalism. This article seeks to integrate the discourse of early modern economics with Cervantes’s poetics. It argues that Don Quijote constitutes an experimental generic hybrid of the epic and comic theatre, the two established genres that best accommodated economic material, which was understood as the governing of the household within the traditional organization of the family. It thereby proposes a new theory of the econopoetics that structures Cervantes’s epic comedy.